Psychometric Characteristics of Passionate Love Scale ((Field study on a sample of students of theoretical and scientific colleges at Damascus University)) (Journal of Hama University, 2019)
The aim of the current research was to identify the degree of mastery of the sixth grade students in basic science operations in social studies. The sample consisted of (250) students and students, randomly selected from (7) schools in Damascus. The research is an achievement test for basic science operations. It consists of (24) multiple-choice questions. The veracity of the tool has been verified by presenting it to a group of arbitrators. The stability of the tool has been confirmed by a survey sample, (0.70).After applying the tool and analyzing the results, the researcher reached a low level of mastery of the sixth grade students for the basic science operations in general. The percentage of proficiency was (52.17%), which is less than the required limit (70%).After applying the tool and analyzing the results, the low level of mastery of the basic sixth grade students was found in the basic science operations in general. The percentage of proficiency reached (52.17%), which is less than the required threshold, (70%).The results of the study showed that there were varying levels of proficiency of the sample for some basic science operations. The sample achieved the level of proficiency in the classification and observation processes in percentages of (83.87%) and (76.13%) respectively, The percentages of temporal and spatial use, inferation, and communication were the lowest in terms of accuracy (14.93%),( 22%) and (39.33%) respectively. Researcher with a number of relevant proposals to continue the research, the most important of which was:1_ descriptive study of the role of teachers in the development of basic science processes of students in the basic education stage. 2_ An analytical study of the books of social studies in the basic education stage; to know the extent of the inclusion of the basic science processes.